Physicochemical and Sensory Characteristics of Ice Cream with Addition of Dayak Onion Extract - Lily Siti Balqis; Rosy Hutami; Intan Kusumaningrum (Universitas Djuanda, 2025)
Dayak onions contain antioxidants that can be utilized in functional foods. Dayak onions also have potential as a natural food coloring. There is a need for research on the addition of dayak onion extract to food products with minimal heat processing such as ice cream to maintain antioxidants and color. The purpose of this study was to determine the effect of the addition of dayak onion extract on the physicochemical and sensory characteristics of ice cream. The method used was Completely Randomized Design 1 factor with 4 treatment levels namely P0 (0%), P1 (0.25%), P2 (0.5%), and P3 (0.75%). Based on the analysis of variance, the addition of dayak onion extract gave a significant effect on lightness, a* value, b* value, pH, antioxidant activity, color, taste, aftertaste, and overall impression of ice cream at a significance level of 0.05 (p<0.5). However, the addition of dayak onion extract did not significantly affect the overrun, melting time, water content, ash content, protein content, fat content, carbohydrate content, aroma, and texture of ice cream. The selected ice cream product with the addition of dayak onion extract is P1 (0.25%) with careys pink color, lightness 75.02, a* value 12.34, b* value 9.40, overrun 46.29%, melting time 17.29 minutes, pH 6.343, and showed very weak antioxidant activity with 481.35 mg/L IC50 value. The total energy of ice cream with the addition of selected dayak onion extract obtained from fat, protein, and carbohydrates amounted to 88.07 kcal from a serving size of 60 g.